(untitled) (Gestão & Regionalidade, 2022)
The company, object of this study, operates in the personal hygiene segment and is the Market leader. It offers products that meet the needs of 1.5 billion people around the world and had losses of finished products due to non-compliance. The objetctive was to study quality as a support to reduce waste. An action research was carried out. As a source of data the sectors of quality and production were used. Between january and april 2017 there were 473,280 units of absorbent rejected by tears. Possible causes of the problem: lack of operational knowledge regarding quality, failure in machine performance and non-compliant raw material. Interventions were made to solve possible problems. When examining the raw material, it was found non-compliance, a fact that caused waste and loss of R 176,398.00 with raw material and finished products. After the intervention the losses was zeroed. Companies must continually assess their suppliers, regardless of having ISO 9001.